A Robust Approach to Vision-Based Terrain-Aided Localization - Dan Navon; Ehud Rivlin; Hector Rotstein (Navigation)
Terrain-aided navigation, which combines radar altitude with a digital terrain map (DTM), was developed before the era of the Global Positioning System to prevent error growth resulting from inertial navigation. Recently, cameras and substantial computational power have become ubiquitous in flying platforms, prompting interest in studying whether the radar altimeter can be replaced by a visual sensor.